Anti-Fandom: Dislike and Hate in the Digital Age, Melissa A. Click (ed.) (2018). (1st June 2020) - Sheldon, Zachary
Review of: Anti-Fandom: Dislike and Hate in the Digital Age, Melissa A. Click (ed.) (2018)New York: New York University Press, 352 pp., ISBN 978-1-47985-104-1, p/bk, $30.00